PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 7E TERHADAP HASIL BELAJAR KIMIA DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS SISWA - Patmah -; Agus Abhi Purwoko; Muntari - (Jurnal Penelitian Pendidikan IPA, 2017)
This study aimed to: (1) determine the effect of Learning Cycle 7E model and conventional model towards student’s learning outcomes of Chemistry, (2) determine the effect of the critical thinking skills towards student’s learning outcomes of Chemistry, and (3 ) determine the interaction between the learning model (learning Cycle 7E-Conventional) with the critical thinking skills (High - Low) towards student’s learning outcomes of Chemistry. This research is a Quasi Experiment with the 2 x 2 factorial design and variables in this research consists of independent variables, moderator variables and the dependent variable. Learning Cycle Model 7E and conventional learning models used as independent variables, critical thinking skills students used as the moderator variable, and the learning outcomes used as the dependent variable. Analysis of the research’s results using by Two Way ANACOVA at the level 5% of significance. According to the results of analysis, it was concluded that the critical thinking skills significantly influence on chemistry student learning outcomes, where the average of high group of critical thinking skills, significantly higher than lower group.Keywords: Learning cycle 7E model, critical thinking skills, chemistry learning outcomes